Methodology and Initial Results From a Real-World Observational Cohort of Patients With Inflammatory Bowel Disease: TARGET-IBD. Issue 3 (13th May 2021) - Click, Benjamin; Barnes, Edward L; Cohen, Benjamin L; Sands, Bruce E; Hanson, John S; Regueiro, Miguel; Rubin, David T; Dubinsky, Marla C; Gazis, Derek R; Dalfonso, Laura; Hildebrand, Janet S; Crawford, Julie M; et al.
Abstract: Background: Data on care patterns for inflammatory bowel disease (IBD) from large-scale, diverse clinical cohorts in real-world practice are sparse. We developed a real-world cohort of patients receiving care at academic and community sites, for comparative study of therapies and natural history of IBD. Methods: We describe novel methodology of central abstraction of clinical data into a real-world IBD registry with patient reported outcomes (PROs). Baseline demographics, clinical characteristics, healthcare utilization, and disease metrics were assessed. Bivariate statistics were used to compare demographic and clinical data by Crohn disease (CD) or ulcerative colitis (UC) and site of care (academic, community). Results: In 1 year, 1343 IBD patients (60.1% CD, 38.9% UC) were recruited from 27 academic (49.5%) and community (50.5%) sites, exceeding expectations (110% enrolled). Most participants also consented to provide PROs (59.5%) or biosamples (85.7%). Overall, 48.7% of the cohort provided a baseline PRO, and 62.6% provided a biosample. Compared to UC, CD subjects had higher prior (34.1% CD vs 7.7% UC; P < 0.001) and current (72.1% vs 47.9%; P < 0.001) biologic utilization. CD participants from academic sites had more complicated disease than those from community sites (62.5% vs 46.8% stricturing/penetrating; 33.5% vs 27% perianal; 36.8% vs 14.5% prior biologic, respectively). Nearly all (90.4%) participants had endoscopic data of whom 37.7% were in remission. One-year retention was 98.4%. Conclusions: Centralized data abstraction and electronic PRO capture provided efficient recruitment into a large real-world observational cohort. This novel platform provides a resource for clinical outcomes and comparative effectiveness research in IBD. Lay Summary: Data on inflammatory bowel disease (IBD) care patterns in the real-world setting are sparse. This real-world cohort of patients with IBD receiving care at academic or community sites provides a novel platform to study treatment pattern differences and clinical outcomes.